Determinants of Banking Service Quality and Their Impact on Customers’ Patronage in Retail Banking in India - Kumar, Prashant (Digital Repository of Theses, 2025)
This study examines at the key variables of banking service quality and how they affect consumer patronage in Indian retail banking. To investigate the relationships between banking service quality and customer patronage, data from 425 respondents was collected from Maharashtra state. According to the demographic information, the majority of respondents are married and male, and the population is under 30 years of age group. The majority of the respondents have graduate degrees, indicating a highly educated group. Respondents are mostly from the districts of Thane and Pune, and the occupation profile is dominated by self-employed and in the private sector. As a result of hypotheses testing, all four determinants of service quality and consumer patronage were found to be significantly correlated, with staff conduct showing the strongest relationship (r = 0.726). Customer patronage also demonstrated favourable relationships with other determinants, including communication (r = 0.568), credibility (r = 0.500), and access to teller services (r = 0.618). The direct impact of these elements was further supported by path analysis, which showed that customer patronage was most significantly influenced by staff conduct (coefficient = 0.394) and communication (coefficient = 0.300), followed by credibility and access to teller services. The results indicate that customer patronage and retention can be significantly increased by improving the behaviour of workers, encouraging clear communication, boosting bank credibility, and making teller services more easily accessible. The study supports earlier research that emphasises the role that customer satisfaction, service quality, and trust play in promoting customer patronage. The study sheds light on how India's retail banks may raise customer patronage by enhancing service quality. Key Words: Service Quality, Customers’ Patronage, Retail Banking, Indian Banking.